Reproductive health of male Australian veterans of the 1991 Gulf War - Glass Deborah C; McKenzie Dean P; Forbes Andrew B; Ikin Jillian F; Sim Malcolm R; Kelsall Helen L; Ittak Peter (BMC, 2007)
Abstract Background Since the 1991 Gulf War concerns have been raised about the effects of deployment to the Gulf War on veterans' health. Studies of the reproductive health of Gulf War veterans have reported varied findings. Methods We undertook a cross-sectional study of male Australian Gulf War veterans (n = 1,424) and a randomly sampled military comparison group (n = 1,548). The study was conducted from August 2000 to April 2002. A postal questionnaire included questions about difficulties achieving pregnancy, pregnancy outcomes including live births, stillbirths, miscarriages and terminations; and for all live births gestation, birth weight, sex, and any cancers, birth defects, chromosomal abnormalities or serious health problems. Results Male Gulf War veterans reported slightly increased risk of fertility difficulties following the Gulf War (odds ratio [OR] 1.4; 95% confidence interval [CI] 1.0-1.8), but were more successful at subsequently fathering a child (OR 1.8; 95% CI 1.3-2.6). The study groups reported similar rates of pregnancies and live births. There was no increased risk in veterans of miscarriage, stillbirth, or terminations. Children of male Gulf War veterans born after the period of the Gulf War were not at greater risk of being born prematurely, having a low birth weight, or having a birth defect or chromosomal abnormality (OR 1.0; 95% CI 0.6-1.6). The numbers of cancers and deaths in children were too small to draw any firm conclusions. Conclusion The results of this study do not show an increased risk of adverse reproductive outcome in Australian male Gulf War veterans.